2021
DOI: 10.3390/molecules26216672
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure Engineering of Metal–Organic Derived Frameworks: Cobalt Phosphide Embedded in Carbon Nanotubes as an Efficient ORR Catalyst

Abstract: Heteroatom doping is considered an efficient strategy when tuning the electronic and structural modulation of catalysts to achieve improved performance towards renewable energy applications. Herein, we synthesized a series of carbon-based hierarchical nanostructures through the controlled pyrolysis of Co-MOF (metal organic framework) precursors followed by in situ phosphidation. Two kinds of catalysts were prepared: metal nanoparticles embedded in carbon nanotubes, and metal nanoparticles dispersed on the carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 42 publications
(41 reference statements)
1
9
0
Order By: Relevance
“…The ORR kinetics mechanism can be revealed using linear sweep voltammetry (LSV) test electrode polarization curve and the Tafel slope b fitted by the Tafel formula (Equation ( 8)) [50]. As shown in Figure 4a, the Tafel slope of MOF-525-Fe/Zr is 42 mV/dec, which is significantly lower than that of MOF-525 (74 mV/dec) as well as some commercial ORR electrocatalysts, such as Pt/C (86 mV/dec) and IrO 2 (120 mV/dec) and the Pt/Pd/Co-NC (74 mV/dec) [51,52]. The comparison results show that MOF-525-Fe/Zr has lower ORR resistance and higher charge transfer rate, which can efficiently reduce O 2 to produce an active oxidant [53].…”
Section: Analysis Of Photoelectric Propertiesmentioning
confidence: 95%
“…The ORR kinetics mechanism can be revealed using linear sweep voltammetry (LSV) test electrode polarization curve and the Tafel slope b fitted by the Tafel formula (Equation ( 8)) [50]. As shown in Figure 4a, the Tafel slope of MOF-525-Fe/Zr is 42 mV/dec, which is significantly lower than that of MOF-525 (74 mV/dec) as well as some commercial ORR electrocatalysts, such as Pt/C (86 mV/dec) and IrO 2 (120 mV/dec) and the Pt/Pd/Co-NC (74 mV/dec) [51,52]. The comparison results show that MOF-525-Fe/Zr has lower ORR resistance and higher charge transfer rate, which can efficiently reduce O 2 to produce an active oxidant [53].…”
Section: Analysis Of Photoelectric Propertiesmentioning
confidence: 95%
“…ZIFs (zeolitic imidazolate frameworks) are a series of MOFs with a zeolite-like framework and intrinsic M-N 4 active sites ( Phan et al, 2010 ; Zhang et al, 2017b ; He et al, 2019 ), which is beneficial to the ORR process and is suitable to be used as a model to explore the exposure of the intrinsic active sites. The popular Co-based ZIF (ZIF-67) has been studied extensively in the ORR, OER (oxygen evolution reaction), and other electrocatalytic processes by high-temperature pyrolysis to its derivatives and exhibited efficient catalytic performance ( Ma et al, 2011 ; Zhao et al, 2014 ; Shah et al, 2017 ; Najam et al, 2019 ; Shah et al, 2021b ; Imran et al, 2022 ), but the catalytic activity of the parent ZIF-67 is poor. In other words, the intrinsic active sites in ZIF-67 are unable to be exposed to promote the catalytic activity under such conditions and need to be activated.…”
Section: Introductionmentioning
confidence: 99%
“…35,38 The reflections of fcc structures accompanied by 2θ values shifted to higher levels in the characteristic peaks due to the incorporation of Ni atoms into the Pt lattice, approving the alloying of Pt and Ni when compared with the PC pattern. 39 pattern when the catalysts have more than 25% Ni content and may exist due to the impurities. 3 The crystallite size is calculated using the Scherrer equation given in Table 1.…”
Section: Morphology and Distribution Analysis Of Pnc Bimetallic Nanop...mentioning
confidence: 99%
“…30 Do et al have confirmed that the EASA decreases with increasing the Ni metal content in the PNC electrocatalysts, demonstrating the link between particle size, EASA, and electrocatalyst composition. 39 Figure 7 shows the OCP of different PNC cathodes measured in the 0.1 to 0.6 V range against NHE. The OCP is found to decrease as the Ni metal percentage in PNC electrodes increases.…”
Section: The Orr Activity Of Various Combinations Of Pnc Bimetallic E...mentioning
confidence: 99%